Women’s Activism in the Islamic Republic of Iran Political Alliance and the Formation of Deliberative Civil Society - Ghoreishi, Samira (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
XIII, 192 p. 2 illus. in color.